Production of an exopolysaccharide by Antarctic yeast - Pavlova, K; Panchev, I; Krachanova, M; Gocheva, M (Folia microbiologica, 2009)
Psychrophilic Antarctic yeasts produce polysaccharides in different concentrations. According to morphological, cultural, physiological and biochemical characteristics, the best producer strain was identified as Cryptococcus flavus A(51). The highest values for viscosity (59.1 mPa s) and crude polysaccharide productivity (5.75 g/L) were obtained in a medium containing 5 % sucrose and 0.25 % (NH(4))(2)SO(4), at 24 degrees C for 6 d. The chemical composition and sugar constituents of the crude exopolysaccharide were determined (92.5 % saccharides, 3.34 % protein, and 4.16 % ash). The monosaccharide composition of the exopolysaccharide obtained from C. flavus strain AL(51) was established (55.1 % mannose, 26.1 % glucose, 9.60 % xylose, 1.90 % galactose). The microbial biopolymer has a high molar mass and homogeneity: 82 % of it had M 1.01 MDa.
Keywords: Yeasts; polysacharidy; zvířata; Antarktida; Spheniscidae; kvasinky; Polysaccharides; Antarctic Regions; Animals